Миниатюра Арцаха-Утика (XIII—XIV вв.) - Г. Г. Акопян (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Մաշտոցի անվան Մատենադարանում պահպանվող Արցախ-Ուտիքի նկարազարդ ձեռագրերը կարելի է բաժանել երկու խմբի։ Deposited in the Mashtots Matenadaran is a number of illustrated manuscripts whose origin is associated with the scriptures of Artsakh-Utik. They are classified into two groups.
Keywords: N Fine Arts; ND Painting